2017
DOI: 10.13063/2327-9214.1263
|View full text |Cite
|
Sign up to set email alerts
|

Active Use of Electronic Health Records (EHRs) and Personal Health Records (PHRs) for Epidemiologic Research: Sample Representativeness and Nonresponse Bias in a Study of Women During Pregnancy

Abstract: Introduction:With the growing use of electronic medical records, electronic health records (EHRs), and personal health records (PHRs) for health care delivery, new opportunities have arisen for population health researchers. Our objective was to characterize PHR users and examine sample representativeness and nonresponse bias in a study of pregnant women recruited via the PHR.Design:Demographic characteristics were examined for PHR users and nonusers. Enrolled study participants (responders, n=187) were then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Prior research has suggested that patient portal users are not demographically representative of the patient population as a whole (reinforced by Figures 2 and 3), in addition to portals presenting challenges to low socioeconomic status (SES) and low literacy patients. [13][14][15] These factors likely also affect the makeup of the populations that receive recruitment messages through the patient portal and ultimately make the choice to enroll. Though we were not able to determine SES or literacy for the patients contacted for ADAPTABLE, Figures 2 and 3 indeed indicate that different methods of contact reach different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has suggested that patient portal users are not demographically representative of the patient population as a whole (reinforced by Figures 2 and 3), in addition to portals presenting challenges to low socioeconomic status (SES) and low literacy patients. [13][14][15] These factors likely also affect the makeup of the populations that receive recruitment messages through the patient portal and ultimately make the choice to enroll. Though we were not able to determine SES or literacy for the patients contacted for ADAPTABLE, Figures 2 and 3 indeed indicate that different methods of contact reach different populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a limitation that some results (e.g., BMI, weight gain, breast feeding) are based on variables available only in recent years of data and may not be relevant to earlier times. However, the use of these data allowed a population-based perspective and included all women with deliveries, regardless of where delivery occurred, race/ethnicity, or other factors often associated with lack of participation in research studies (43).…”
Section: Limitationsmentioning
confidence: 99%
“…Even so, only a minority of institutions responding to our survey had implemented the use of EHR patient portals for research purposes. In addition, there continue to be disparities in individuals' access to and use of EHRs and PHRs, particularly among certain socio-demographic groups [13]; however, this is improving and there is some evidence that underrepresented groups are just as amenable to recruitment via such approaches [14].…”
Section: Discussionmentioning
confidence: 99%